Specific Inhibition of Cell Division by Colicin E(2) Without Degradation of Deoxyribonucleic Acid in a New Colicin Sensitivity Mutant of Escherichia coli - Beppu, Teruhiko (1972)
A new class of colicin sensitivity mutants of Escherichia coli was isolated whose cell division was specifically inhibited by colicin E(2) without detectable degradation of deoxyribonucleic acid (DNA) at 30 C. The mutant could not form colonies in the presence of colicin E(2) but recovered colony-forming ability by trypsin treatment even after prolonged incubation with the colicin. Addition of colicin E(2) to the exponentially growing mutant inhibited cell division completely but did not induce degradation of DNA into cold acid-soluble materials nor any breakage of DNA strands. Synthesis of DNA in the mutant was not inhibited, and long filamentous cells with multiple nuclear bodies were formed by the action of colicin E(2). Degradation of ribosomal ribonucleic acid and development of prophage λ, both of which were induced by colicin E(2) in the sensitive cells, did not occur in the mutant. At the elevated temperature, however, the mutant was found to undergo colicin-induced degradation of DNA. No differences in ultraviolet light nor drug sensitivities were observed in the mutant compared to the parent E. coli. The data suggested that colicin E(2) had a specific inhibitory effect on cell division of E. coli that was not a consequence of DNA degradation.